Pembangkit Listrik Pikotermal Matahari, Kajian Awal - Aulia, Aulia; Darwison, Darwison; Razak, Faisyal; Waldi, Eka Putra (Jurusan Teknik Elektro Universitas Andalas, 2017)
A Picothermal solar power plant (PLTPM) is an original concept that is still under study. Testing and calculation of voltage and electrical current is carried on a single thermoelectric, thermoelectric cells connected in series and parallel connected thermoelectric cells due to rise in temperature in the cells. The results showed that the increase in temperature of 71 Â°C produces 1 volt output voltage and current of 0.1 amperes. In accordance with the principle of series and parallel connection, series connection is able to multiply the output voltage and the parallel connections double the current output for one additional thermoelectric cell chipKeywords : Picothermal, thermoelectric cell and series, parallel, temperatureAbstrakâ€” Pembangkit listrik pikotermal matahari (PLTPM) merupakan konsep awal yang masih dalam tahap kajian. Pengujian dan perhitungan tegangan dan arus listrik dilakukan terhadap termoelektrik tunggal, sel termoelektrik terhubung seri dan sel termoeletrik terhubung paralel akibat kenaikan suhu pada sel-sel tersebut. Hasil memperlihatkan bahwa kenaikan suhu sebesar 71 oCÂ menghasilkan tegangan keluaran 1 volt dan arus 0.1 Amper. Sesuai dengan kaedah hubungan seri dan paralel, hubungan seri mampu melipat gandakan tegangan keluaran dan hubungan paralel melipatkan gandakan arus keluaran untuk tambahan setiap satu keping sel termoelektrik.Kata Kunci : pikotermal, sel termoelektrik, seri, paralel, kenaikan suhu